新加坡双语教育政策的历史产物 ：特别辅助计划的变迁与反思 = A historical product of Singapore's bilingual education policy : the evolution of and reflection on the special assistance plan - 李家莹 Lee, Emelia Jia Ying (2015)
本文主要研究新加坡双语教育政策下，由教育部在1978年11月30日宣布的“特别辅助计划”（Special Assistance Plan）。“特别辅助计划”经历了漫长和复杂的演变过程，随着新加坡教育系统的变化和改革而做出了相应的调整，在培养双语人才和保留华校传统方面贡献不少，因此是政府推行双语教育政策中不可或缺的一部分。 被教育部筛选实行“特别辅助计划”的中学因为是值得保留并发展的好学校，因此被称为特选中学，也肩负起了传承中华文化和知识的重任，是新加坡教育系统下公认的优秀学府。“特别辅助计划”实行至今已有36年，发展脉络复杂，过程中也陆续受到多方的赞赏和质疑。因此，本文将结合新加坡独立后的双语教育政策说明“特别辅助计划”的产生背景与由来，阐述计划的内容与变迁。最后，再对此计划进行反思和探讨。 This paper involves the study of the Special Assistance Plan, which was announced by the Ministry of Education on 30 November 1978 and serves as a cornerstone of the state’s bilingual education policy. To cater to the perennially changing needs and adjustments of Singapore’s education system, the plan has also evolved over the decades, making an indispensible contribution to the nurturing of bilingual talents and preservation of traditional Chinese-medium school culture. The Special Assistance Plan secondary schoolshave undertaken the vital responsibility of inculcating Chinese traditional values in their students, while being recognized as outstanding academic institutions by the government. The historical development of the Special Assistance Plan has been a convoluted process, receiving both acclaim and criticism over the years. Therefore, this paper seeks to explain and clarify the historical background and development of the Special Assistance Plan over the years while reflecting on the plan’s accomplishments, limitations and future possibilities.